Decline of the lung function related to the type of tobacco smoked and inhalation. Issue 1 (January 1990) - Lange, P; Groth, S; Nyboe, J; Mortensen, J; Appleyard, M; Jensen, G; Schnohr, P
Abstract : Data from a five year follow up study on 4372 smokers and 3753 non-smokers were analysed to investigate the influence of the type of tobacco smoked and whether the subjects said they inhaled or not on the decline in forced expiratory volume in one second (FEV1). The study sample comprised 1492 smokers of plain cigarettes and 1936 smokers of filter cigarettes, 1711 smokers of cheroots or cigars, and 233 male pipe smokers. Over the five years, smokers, especially those who said that they inhaled, had a higher rate of decline of FEV1 than non-smokers, in whom the average decline in FEV1 was 25 ml/year for women and 30 ml/year for men. There was no significant difference in the decline in FEV1 between filter cigarette smokers and plain cigarette smokers. The decline in FEV1 in cigar or cheroot smokers was the highest for all the smoking groups, and associated with a very high tobacco consumption in this group. Among pipe smokers who inhaled, the decline in FEV1 was slightly higher than in the cigarette smokers, whereas non-inhaling pipe smokers had a decline in FEV1 that was similar to that of non-smokers. In general, the smokers who said that they did not inhale had a smaller decline in FEV1 than those who said that they did. The effect of inhalation varied in magnitude in different smoking groups, being most pronounced in pipe smokers.